Peroxisome proliferator-activated receptors, farnesoid X receptor, and dual modulating drugs in hypertension - Imig, John D. (Frontiers in Physiology, 2023)
Hypertension characterized by an elevated blood pressure is a cardiovascular disease that afflicts greater than one in every three adults worldwide. Nuclear receptors are large superfamily of DNA-binding transcription factors that target genes to regulate metabolic and cardiovascular function. Drugs have been developed for nuclear receptors such as peroxisome proliferator-activated receptors (PPARα and PPARγ) and farnesoid X receptor (FXR). PPARα, PPARγ, and FXR agonists are used clinically to treat lipid disorders and metabolic diseases. Evidence from clinical studies and animal hypertension models have demonstrated that PPARα, PPARγ, and FXR agonism can lower blood pressure and decrease end organ damage which could be useful for the treatment of hypertension in patients with metabolic diseases. Unfortunately, PPAR and FXR agonists have unwanted clinical side effects. There have been recent developments to limit side effects for PPAR and FXR agonists. Combining PPAR and FXR agonism with soluble epoxide hydrolase (sEH) inhibition or Takeda G protein receptor 5 (TGR5) agonism has been demonstrated in preclinical studies to have actions that would decrease clinical side effects. In addition, these dual modulating drugs have been demonstrated in preclinical studies to have blood pressure lowering, anti-fibrotic, and anti-inflammatory actions. There is now an opportunity to thoroughly test these novel dual modulators in animal models of hypertension associated with metabolic diseases. In particular, these newly developed dual modulating PPAR and FXR drugs could be beneficial for the treatment of metabolic diseases, organ fibrosis, and hypertension.